Using Formative Assessment and Feedback from Student Response Systems (SRS) to Revise Statistics Instruction and Promote Student Growth for All - Grace Pai (Journal of Statistics and Data Science Education)
Instructors are increasingly using interactive student response systems (SRS) to foster active learning and deepen student understanding in statistics education. Yet most studies focus on either the benefits of SRS or on how students can receive and use feedback, rather than on how instructors can use formative assessment data to inform instructional revisions for the purpose of enacting inclusive pedagogy to reach more learners. This article draws from a case study of an introductory statistics course at a community college to detail a framework for how an instructor can engage in what I call a reciprocal formative assessment and feedback cycle using SRS. This cycle is designed to address the goal of increasing equity—as defined by learning growth for all students—through a structured approach of reflecting on student misconceptions to determine who to reteach, what to reteach, when to reteach, and how to reteach course content.